ChemInform Abstract: Sr2FeO3 with Stacked Infinite Chains of FeO4 Square Planes. Issue 29 (1st July 2013) - Tassel, Cedric; Seinberg, Liis; Hayashi, Naoaki; Ganesanpotti, Subodh; Ajiro, Yoshitami; Kobayashi, Yoji; Kageyama, Hiroshi
Abstract: Due to the thermal instability of Sr2 FeO4, Sr2 FeO3 is obtained from the latter in the presence of CaH2 as reducing agent (evacuated Pyrex tubes, 2980 °C, 96 h).